(3GdBOGH GdfGaYI HGdCdaGX GdoeNJGQI GdLGeYIs - (3LYaQ Hf eMeO GHf eNJGQ GdCaVdj, CHh GdaVd, GdedbH eLO Gdoedc , GHf nTreS GdpNndGaI,J (B622 (3g` s ((3jdbWdh Hf YHOGddg s)
(3ChdgG (B:s
(3HYO GdMeO dg(B: (3aEf CdWa GdcdGe ehbYkG, hCTQag ehVYkG cdeI MceI jbJOj GdEfSGf HSfGgG ajgJOj hbO LeYJ aj cJGHj gPG eG jUbd GdNhGWQ GdUOjI hjTMP GdbQGFM GdcGdg s
(3BNQgG (B:s
(3nNpqd ef bd NjQg dc aj GdfGS ZjQg ce fYje fYeJg ZjQ Cfj YOeJg fLR GdcJGH HMeO Gddg hYhfg hefg hcQeg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B128 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B149s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B1 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs